Depression in the wives of convicted men: prevalence and associated factors - Débora Cristina Martins Barbosa; Gabriela Ramos Furman; Aliny de Lima Santos; Carlos Alexandre Molena-Fernandes
ABSTRACT Objective: To estimate the prevalence of depression and to identify the main risk factors associated with depression in wives of convicted men. Method: Descriptive, cross - sectional, quantitative approach. The data were collected with 349 female partners of convicted patients in three penitentiaries in the state of Paraná, with a semistructured research, between January and June of 2016, being compiled in a database and analyzed using SPSS® 20.0 software. Results: It was possible to identify vulnerability to depression among wives of convicted men, most were young and 42.2% have or already had depression. It was verified that the variables to depression were ages equal to or above 30 years (50.3%, p <0.001), smoking (61.1%, p <0.013) and alcoholism (16.1%, p <0.001). Conclusion: It is the responsibility of the nurse with the multidisciplinary health team to invest in health promotion and prevention actions against these risk factors that were associated with depression in this population.